COMPARISON OF HBA1C LEVEL USING TURBIDIMETRY INHIBITION IMMUNOASSAY, LATEX AGGLUTINATION INHIBITION METHOD AND HPLC METHOD - Salmon Sutandra; Asvin Nurulita; Mansyur Arif (Indonesian Association of Clinical Pathologist and Medical laboratory, 2018)
According to the National Glycohemoglobin Standardization Program (NGSP) and The Diabetes Control and Complication Trial(DCCT) the standard method of measuring HbA1c is High-Performance Liquid Chromatography (HPLC), but HPLC requiresparticular instrument investments, trained staff, long and relatively expensive sample processing. This an instrument that hassimilar performance to HPLC but its operation process is relatively simple and not costly. The purpose of this study was to analysethe HbA1c level using Turbidimetry Inhibition Immunoassay (TII) method and the HPLC method; to analyse HbA1 level using LatexAgglutination Inhibition (LAI) method and HPLC method. This research was conducted with a cross-sectional design during theperiod of March-April 2017. The total sample consisted of 160 samples divided into two groups. For the first group, HbA1c levelusing TII method and HPLC method was measured. For the second group, HbA1c level was measured using LAI method and HPLCmethod.The data obtained were analyzed using the Paired T-test. There was a significant difference between HbA1c levels usingTII method and HPLC method 8.12(2.53)% vs. 8.49(2.63)%, p<0.001. There was no significant differences between HbA1c levelsusing LAI method and HPLC method 7.52(1.95%) vs. 7.47(2.00)%, p>0.05. This research concluded that there was a differencebetween the HbA1c levels using TII method and HPLC method, but no difference between HbA1c levels using LAI method and HPLC method.